Computer graphics. Proceedings CD-ROM SIGGRAPH 97, 3-8 August 1997, Los Angeles, California USA. - SIGGRAPH (Conference) (1997 Los Angeles, Calif); SIGGRAPH ([New York, N.Y.] ACM SIGGRAPH, 1997)
Compact and portable record of the Papers and Panels presentations made at SIGGRAPH 97. This portion of the technical program includes 48 papers, 16 panels, and one special session selected from 265 paper ;and 37 panel submissions.
Title from disc label.
Material is presented in Adobe Acrobat, HTML, MPEG and QuickTime format. Adobe Acrobat Reader software for a wide variety of systems is included, and all Adobe Acrobat documents are indexed with Adobe Acrobat Search for easy keyword searching. It is a Macintosh/ISO 9660 hybrid CD-ROM and is mountable on most computer systems.
System requirements: Most computer systems with CD-ROM drives; works best with Windows and Macintosh systems.
Keywords: Computer graphics -- Congresses; Interactive computer systems -- Congresses